Prevalence and associated factors of undernutrition among pregnant women visiting ANC clinics in Silte zone, Southern Ethiopia - Mohammed Muze; Mubarek Yesse; Shemsu Kedir; Abdilmejid Mustefa (BMC, 2020)
Abstract Background Maternal undernutrition is highly prevalent in underdeveloped countries. Hence, this study was intended to determine the prevalence and associated factors of undernutrition among pregnant women visiting ANC clinics in Silte Zone. Method Facility-based cross-sectional study was conducted from July to January 2019. Systematic random sampling technique was used to select 422 study participants from 11 randomly selected health facilities. Data was collected by using a structured-interviewer administered questionnaire. Mid upper arm circumference (MUAC) was measured by standard non stretchable MUAC tape. Data was entered into a computer using Epi data 3.1 and edited, cleaned, and analyzed using SPSS version 20. Both bivariate and multiple logistic regression analyses were employed to identify factors associated with maternal undernutrition. Result In this study, the overall prevalence of undernutrition among study subjects was 21.8%. Age greater than 31 years of women (AOR = 0.15; 95% CI: 0.03, 0.93), Birth intervals > 2 years (AOR = 0.18; 95% CI: 0.04, 0.76), good nutritional knowledge (AOR = 0.34; 95% CI: 0.17, 0.67), and having no dietary change as a result of current pregnancy AOR = 6.02; 95% CI: 2.99, 12.14) were significantly associated with undernutrition. Conclusions The prevalence of undernutrition among pregnant women was 21.8%. Current estimate is lower than previously reported in the study area but higher than reported in developed country. Age of women, Birth intervals, and Dietary change as a result of current pregnancy and Nutrition knowledge were important risk factors/ predictors of undernutrition (MUAC < 23 cm). Interventions targeting maternal nutrition education and child spacing with giving special emphasis to adolescent pregnant women are recommended.